Prostatic dystrophic calcification following salvage cryotherapy for prostate cancer – an under-reported entity?. (2nd January 2021) - Lavi, Arnon; Nair, Shiva M.; Halstuch, Daniel; Chin, Joseph L.
Abstract: Background: Salvage cryoablation (SCA) is an accepted treatment for radio-recurrent prostate cancer with well-established oncological and functional outcomes. Based on one of the longest reported prospective follow-ups in the literature (median 12 years) on 187 patients, this study reports what appears to be an under-appreciated finding in eight patients with dystrophic calcifications (DC) of the prostate following SCA, causing severe bladder outlet obstruction. Materials and methods: Between 1995 and 2004, 187 patients underwent SCA, with a median follow-up of 12 years. This database was reviewed for functional and oncological outcomes and DC were evaluated. Results: Functional data was available in 85 patients, amongst whom eight patients were found to develop DC (9.4%) proven when the patients presented with urinary difficulties and attempted transurethral resection was undertaken for bladder outlet obstruction. Mean time for emergence of significant symptoms of bladder outlet obstruction was 8.6 years from SCA (standard deviation (SD) = 6 years). All eightpatients required permanent drainage (seven suprapubic catheters, one nephrostomy). All patients with DC experienced biochemical recurrence (BCR), compared to 57.1% of the patients with no DC ( p  = 0.01). Conclusion: DC following SCA appears to be an under-reported late adverse effect which may only become evident with long follow-up, and should be included in preoperative counselling.